Plasma environment effects on K lines of astrophysical interest: V. Universal formulae for ionization potential and K-threshold shifts - Palmeri, P.; Deprince, J.; Bautista, M. A.; Fritzsche, S.; Garcia, Javier; Kallman, T. R.; Mendoza, C.; Quinet, P. (Astronomy & Astrophysics, 2022)
Aims. We calculate the plasma environment effects on the ionization potentials (IPs) and K-thresholds used in the modeling of K lines for all the ions belonging to the isonuclear sequences of abundant elements apart from oxygen and iron, namely: carbon, silicon, calcium, chromium, and nickel. These calculations are used to extend the data points for the fits of the universal formulae, first proposed in our fourth paper of this series, to predict the IP and K-threshold lowerings in any elemental ion. Methods. We used the fully relativistic multi-configuration Dirac-Fock method and approximated the plasma electron-nucleus and electron-electron screenings with a time-averaged Debye-Hückel potential. Results. We report the modified ionization potentials and K-threshold energies for plasmas characterized by electron temperatures and densities in the ranges of 105-107 K and 1018-1022 cm-3. In addition, the improved universal fitting formulae are obtained. Conclusions. We conclude that since explicit calculations of the atomic structures for each ion of each element under different plasma conditions is impractical, the use of these universal formulae for predicting the IP and K-threshold lowerings in plasma modeling codes is still recommended. However, their comparatively moderate to low accuracies may affect the predicted opacities with regard to certain cases under extreme plasma conditions that are characterized by a plasma screening parameter of μ > 0.2 a.u., especially for the K-thresholds.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Atomic data; Black hole physics; Plasmas; X-rays: general